Answer:
They're the exact same, except for the variables.
Step-by-step explanation:
Since the variable can be any letter, it is the exact same equation but with different letters as x. Although the equation of G(y) has a y instead of x, you know y is the x and g(y) is the y because the y inside of the parentheses tells us that y is the independent variable.
Hi
Left to do 40% of the shopping
12 items ⇒ 60% of the items
x items ⇒ 40% of the items
60x = 12(40)
60x = 480
x = 480/60
x = 48/6
x = 8 items
Answer:
Left 8 items of the list (40% of the shopping)
Items: 12+8 = 20 items on her list
Rewrite it in the form a^2 - b^2, where a = 5x and b = 8
(5x)^2 - 8^2
Use the Difference of Squares; a^2 - b^2 = (a + b)(a - b)
<u>= C. (5x - 8)(5x + 8)</u>
Answer: x-y=2
Step-by-step explanation:
y+5=x+3; move variable (x) to the left-hand side and change the sign.
y-x+5=3; move the constant to the right-hand side & change the sign
y+x=3-5; reorder the terms
-x+y=3-5; calculate
-x+y=-2; change the signs on both sides
x-y=2 is your answer! hope this helps!
Answer:
3(2-2) * 3(20-2)
3(0) * 3(18)
0 * 54 = 0
Step-by-step explanation:
3(2-2) * 3(20-2)
3(0) * 3(18)
0 * 54 = 0